Penerapan Akupresure Terhadap Diare Pada Anak Toodler dengan Gastroenteritis di Ruang Melati Rumah Sakit Dustira : Case Report - Mulyati, Rini; Nurusabila, Handa (JURNAL KESEHATAN KARTIKA, 2024)
Background: Gastroenteritis is inflammation that occurs in the digestive tract, namely the mucosa of the stomach and small intestine. One of the symptoms of gastroenteritis is diarrhea. Diarrhea is the second cause of death in children under five, and was the cause of the deaths of 370,000 children in 2019. One action that can reduce the frequency of diarrhea is the acupressure technique. Method: The method of this case study is a case report in the form of maintenance by applying evidence-based nursing to patients who are managing acute gastroenteritis who are experiencing diarrhea problems by applying acupressure techniques for 2 days with data collection techniques of interviews, observation, physical examination and documentation study. The technique was carried out for 2 days with 2 meetings each day in the morning and evening with a duration of 1 minute at the points St 36, Cv 12, Bl 25, and Li 4 using the tonification technique. The inclusion criteria for this acupressure technique are children aged 0-5 years, children with acute diarrhea problems, given pharmacological therapy and with parental consent. Results: It was found that the frequency of defecation before the acupressure technique was carried out was liquid defecation 5 times, after acupressure therapy the frequency of defecation was reduced to 3 times. Conclusion: After implementing EBN, acupressure was proven to reduce the frequency of defecation in gastroenteric patients.